The Role of Regional Government on Increasing Awareness of Legal Intellectual Property Rights Education and Education Personnel - Atsar, Abdul; Fitriyana, Wahyudin (Pandecta Research Law Journal, 2018)
This study aims to find out and analyze what factors are causing a lack of awareness of educators and education personnel in Karawang Regency to register intellectual property rights; The impact of not registering the intellectual property rights of educators and education staff in Karawang regency and knowing the efforts made by the local government in increasing the awareness of legal IPR education and education personnel in Karawang Regency. The method in this study is to use an empirical juridical approach. The results of this study indicate that the factors that led to a lack of awareness of educators and education personnel in Karawang Regency to register IPRs were a lack of understanding of educators and education staff about the legal rules of intellectual property rights; Most educators and education personnel do not know what IPR is; Awards for IPR and compliance with IPR laws are still low.Penelitian ini bertujuan untuk mengetahui dan menganalisis faktor-faktor apa yang menyebabkan kurangnya kesadaran pendidik dan tenaga kependidikan di Kabupaten Karawang untuk mendaftarkan hak kekayaan intelektual; Selanjutnya, dianalisis mengenai dampak dari tidak mendaftarkan hak kekayaan intelektual para pendidik dan staf pendidikan di Kabupaten Karawang, serta dimaksudkan juga untuk mengetahui upaya yang dilakukan oleh pemerintah daerah dalam meningkatkan kesadaran hukum pendidik dan tenaga kependidikan tentang Hak Kekayaan Intelektual di Kabupaten Karawang. Penelitian ini menggunakan pendekatan yuridis empiris. Hasil penelitian ini menunjukkan bahwa faktor-faktor yang menyebabkan kurangnya kesadaran pendidik dan tenaga kependidikan di Kabupaten Karawang untuk mendaftarkan Hak Kekayaan Intelektual adalah kurangnya pemahaman pendidik dan staf pendidikan tentang aturan hukum hak kekayaan intelektual; Sebagian besar pendidik dan tenaga kependidikan tidak tahu apa itu Intellectual Property Rights. Selain itu, penghargaan untuk Hak Kekayaan Intelektual dan kepatuhan terhadap hukum Hak Kekayaan Intelektual masih rendah.